I{EFOIWASI DAN REORIENTASI PENDIDIKAN DI·LEMBAGA PENDIDIKAN ISLAM - Jailani, Jailani (Jurnal Cakrawala Pendidikan, 2016)
'rhe nUldrasah as a subsystenlin the national cducatiollul systeJn has heen facing arious problenls, S()I1IC rl'sulting fnull such an external cause as glohalizatioll and SOUle others froln such internal causes as lilnitations of human resources and the ratification of Law No. 22 of 1999. Among the efforts to solve the prOOlCI11S are refonnation and reorientation of the educational system in the institution. Some of the reformation involves the policies taken by the institution in matters such as decisions on future fornlats and options· in affiliations with· the Department of National Education or the Department of Religion with the various consequences and implications (including equality ofoutput with that of public schools). Other efforts take the form of ilnprovenlents of human resources through various breakthroughs), the establishment of model madrasahs and integrated madrasahs, etc. The reorientation ofthe Islamic education at themadrnsahis' done among others by making reorderingsin its "mission, vision, and function and through diversifications of. its departments and course programs (formerly dominatc'd by course programs on religion, . now consisting also of course programs on general subjects, skills, 'and vocations) while still retaining its specific characteristics. Jt is hoped that these efforts can be the early solutions in responding to the challenges of the future ittHI fhtt tthtt ntiutH1J iit~fiHUiou tUIl pIny fl hlgger paU in the preparation of human resources possessing cOlnpctitive competence and added values - mastery of science and technology and possession of cOlnnlendable morals.